2001
DOI: 10.1016/s0022-5347(05)65711-4
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Prepubic Sinus: A Variant of Dorsal Urethral Duplication Suggested by Immunohistochemical Analysis

Abstract: The existence of transitional epithelium in the proximal part of the sinus and presence of smooth muscle bundles around it reinforce the theory that congenital prepubic sinus is a variant form of dorsal urethral duplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 10 publications
0
15
0
2
Order By: Relevance
“…Multiple theories have been proposed to explain the embryological aetiology for congenital prepubic sinus, among which the theory suggesting that it is a variant of urethral duplication predominates 7. In our case, patient’s anomaly was similar to the type IA variant of Effman’s classification suggesting it to be a variant of epispadiac urethral duplication.…”
Section: Discussionmentioning
confidence: 51%
“…Multiple theories have been proposed to explain the embryological aetiology for congenital prepubic sinus, among which the theory suggesting that it is a variant of urethral duplication predominates 7. In our case, patient’s anomaly was similar to the type IA variant of Effman’s classification suggesting it to be a variant of epispadiac urethral duplication.…”
Section: Discussionmentioning
confidence: 51%
“…However, Huang et al . reported that the immunohistochemical study revealed the lining epithelium was transitional proximally and squamous distally in five patients with congenital prepubic sinus and reinforced the theory that congenital prepubic sinus is a variant form of dorsal urethral duplication 4 …”
Section: Discussionmentioning
confidence: 67%
“…Urethral duplication most often occurs in the sagittal plane, and if blind-ending is referred to as a pre-pubic sinus [2]. Bladder duplication is most often complete versus incomplete, in which the bladders are separate entities and drained by separate urethras [3].…”
Section: Resultsmentioning
confidence: 99%